Implementasi Kurikulum Merdeka Pada Cara Belajar Siswa Untuk Semua Mata Pelajaran (Studi Kasus Pembelajaran Tatap Muka di SMK INFOKOM Bogor) - Mila Yaelasari; Vera Yuni Astuti (Jurnal Pendidikan Indonesia, 2022)
This study discusses about implementation of an independent curriculum on student learning for all subjects (a case study of face-to-face learning at SMK INFOKOM Bogor). In the development of education in Indonesia, the quality of education is influenced by the educational curriculum applied at the level of the education unit, starting at the basic education level, elementary, junior high, high school/vocational school to higher education, university education. This is the background of researchers taking research on the implementation of the independent curriculum. Which in Indonesia the education curriculum often changes following the change of the minister of education starting from the KTSP curriculum (Education Unit Level Curriculum), 2013 curriculum, and now the independent curriculum. With the frequent changes in the curriculum used at the education unit level, this will affect the way students learn for all subjects. Hoping that students can understand the lessons learned more quickly from the teacher. However, in implementing the independent curriculum, students become less effective and the social level is increasingly limited and emphasizes individual attitudes. In Indonesia, there are many cultures and varying levels of intelligence, so that the independent curriculum cannot be applied as a whole due to many differentiating variations. To get around the differentiating variations that affect student learning outcomes obtained in face-to-face learning, teachers apply various ways of learning to students. With the hope that it will make students enthusiastic about learning and the grades obtained by students will improve